Clinical and Molecular Features of Hürthle Cell Carcinoma of the Thyroid - Chindris, Ana-Maria; Casler, John D.; Bernet, Victor J.; Rivera, Michael; Thomas, Colleen; Kachergus, Jennifer M.; Necela, Brian M.; Hay, Ian D.; Westphal, Sydney A.; Grant, Clive S.; Thompson, Geoffrey B.; Schlinkert, Richard T.; et al. (The journal of clinical endocrinology and metabolism, 2015)
Context:Hürthle cell cancer (HCC) of the thyroid remains the subject of controversy with respect to natural course, treatment, and follow-up.Objective:The objective of the study was to evaluate the clinical and molecular features associated with outcome in HCC.Design:The study was a review of 173 HCC cases treated at Mayo Clinic over 11 years with a median 5.8-year follow-up.Results:None of the patients with minimally invasive histology had persistent disease, clinical recurrence, or disease-related death. Male gender and TNM stage were independently associated with increased risk of clinical recurrence or death in widely invasive patients. The 5-year cumulative probability of clinical recurrence or death was higher in patients with TNM stage III–IV (females, 74%; males, 91%) compared with patients with TNM stage I–II (females, 0%; males, 17%). Pulmonary metastases were best identified by computed tomography, whereas radioactive iodine scans were positive in only two of 27 cases. Thyroglobulin was detectable in patients with clinical disease, with the notable exception of five patients with distant metastases. The common TERT C228T promoter mutation was detected in both widely invasive and minimally invasive tumors. TERT mRNA was below the limit of detection in all samples.Conclusion:Widely invasive HCC with TNM stage III–IV is aggressive, with low probability of recurrence-free survival. Males have worse outcomes than females. Minimally invasive HCC appears to be considerably less aggressive. Radioactive iodine scan performs poorly in detecting distant disease. Although the TERT gene is mutated in HCC, the role of this mutation remains to be demonstrated.